How to continue COVID-19 vaccine clinical trials? The ethics of vaccine research in a time of pandemic. (March 2022) - Ceruti, Silvia; Cosentino, Marco; Picozzi, Mario
Between December 2020 and March 2021, the US Food and Drug Administration and the European Medicines Agency issued Emergency Use Authorizations and Conditional Marketing Authorizations for the distribution of the first COVID-19 vaccines. Although these vaccines were thoroughly assessed before their approval, regulators required companies to continue ongoing placebo-controlled clinical trials in order to gather further reliable scientific information on their safety and efficacy, as well as to start new studies to evaluate additional candidates. The aim of this paper is to present and discuss the ethical issues raised by the tension between the need to continue these types of clinical trials and the obligations related to the protection of the rights and well-being of research participants. Specifically, we question whether—how, and to what extent—fundamental principles governing research involving human beings can be applied to the current pandemic situation. We argue that continuing ongoing placebo-controlled clinical trials can be considered ethically justifiable only if all participants are adequately informed of any developments that may affect their willingness to remain enrolled, including the current situation of resource scarcity and the prioritization criteria established for vaccination. However, we also argue that currently approved vaccines, which are considered safe and effective enough to be administered to millions of people as part of the vaccination campaign, necessarily represent the "best proven intervention" currently available and, therefore, should be used as comparators in future studies instead of placebo.